Exchange rate bands of inaction and hysteresis in EU exports to the global economy: The role of uncertainty - Ansgar Belke; Dominik Kronen (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
This paper estimates the role of policy and exchange rate uncertainty shocks for EU countries' exports to the world economy. We examine the performance of the four biggest economies, namely Germany, France, Italy and the UK, under policy and exchange rate uncertainty in exports to some of the most important global export destinations (United States, Japan, Brazil, Russia, and China). For this purpose, we apply a non-linear model, where suddenly strong spurts of exports occur when changes of the exchange rate go beyond a zone of inaction, which we call "play" area - analogous to mechanical play. We implement an algorithm describing path-dependent play-hysteresis into a regression framework. The hysteretic impact of real exchange rates on exports is estimated based on the period from 1995M1 to 2015M12. Looking at some of the main export destinations of our selected EU member countries, the United States, Japan and some of the BRICs (Brazil, Russia and China), we identify significant hysteretic effects for a large part of the EU member countries' exports. We find that their export activity is characterized by "bands of inaction" with respect to changes in the real exchange. – – Dieses Papier schätzt die Bedeutung von Schocks in politischer und Wechselkursunsicherheit für Exporte aus EU Ländern in die Weltwirtschaft ein. Wir untersuchen die Performance in Anwesenheit von politischer Unsicherheit und Wechselkursunsicherheit für die vier größten EU Staaten, also Deutschland, Frankreich, Italien und Großbritannien, anhand einiger der wichtigsten Exportdestinationen (USA, Japan, Brasilien und China). Dafür wenden wir ein nicht lineares Modell an, in welchem starke Reaktionen der Exporte auftreten, wenn der Wechselkurs eine inaktive Zone überschreitet, welche von uns "Spielbereich" genannt wird. Wir integrieren einen Algorithmus, der pfadabhängige Hysterese beschreibt, in ein Regressionsmodell. Der hysteretische Effekt des realen Wechselkurses auf Exporte wird für den Zeitraum von 1995 bis Ende 2015 geschätzt. Bei der Betrachtung einiger der wichtigsten Exportdestinationen der berücksichtigten EU Staaten, in diesem Falle den USA, Japan und Teile der BRICs (Brasilien, Russland und China), finden wir hysteretische Effekte für einen Großteil der Exporte aus den EU Staaten.
Keywords: F14; C51; 330; export demand; global economy; hysteresis; policy uncertainty; BRICs; playhysteresis; real exchange rate; switching/spline regression